Building a Media Business: Case Study of the Journey of Kamiya Jani and ‘Curly Tales’ - Mishra, Sreetama (Unisia, 2024)
In recent years, the advent and widespread use of social media platforms have led to significant changes in various aspects of society, including gender dynamics. Presently, social media has emerged as a powerful platform for entrepreneurs to showcase their ventures, connect with their audiences, and build their brands. This study explores the multifaceted role of social media in empowering women across different spheres of life. The emergence of social media platforms has revolutionized the way businesses operate, providing unique opportunities for entrepreneurship. This study explores the role of social media in empowering women entrepreneurs by examining the strategies, challenges, and outcomes of these entrepreneurs in utilizing social media platforms for their business growth. Using this methodology, this study aims to uncover the ways in which women entrepreneurs utilize social media to overcome traditional barriers, enhance visibility, access resources, and build networks. The findings highlight the significant impact of social media on women’s entrepreneurial journeys, offering insights into effective strategies and best practices for leveraging these platforms. This case study delves into the remarkable journey of Kamiya Jani, a prominent figure in the Indian digital content creation space, and her venture "Curly Tales" and her brainchild, Fork Media Group, has carved a niche for itself in the ever-evolving digital landscape, redefining content creation and consumption in India. From humble beginnings to becoming one of the most influential travel and lifestyle content creators in India, her story offers insights into the evolution of digital media and the strategies employed to build a successful YouTube channel and media business.